The Idea of Structuring National Legislation Based on The Ratio of Decidendi & Obiter Dictum Constitutional Court Decision: Gagasan Penataan Legislasi Nasional Berbasis Ratio Decidendi dan Obiter Dictum Putusan Mahkamah Konstitusi - Yuniar Riza Hakiki; Taufiqurrahman Taufiqurrahman (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
MK decission which are